Social work with lesbians and gay men - Brown, Helen Cosis; Cocker, Christine (London SAGE, 2011)
Working with lesbians and gay men is a largely neglected area of social work practice. This book provides social workers and other professionals with an overview of a number of key challenges and concerns that play a significant part in the lives of lesbians and gay men. Despite positive changes in legislation, social work can still fail to meet the needs of lesbians and gay men, and remains a marginalised area in practice, research and teaching. This book promotes an understanding of these issues and proposes ideas for social work practice that are inclusive of lesbians and gay men in assessment and the provision of services. --Book Jacket.
Overview of the historical and contemporary discourses influencing social work with lesbians and gay men -- The legal and policy framework for practice -- Social work values and ethical practice: moving beyond anti-discriminatory or anti-oppressive practice -- Family and kinship and their relationship to social work practice -- Homosexuality, religion and social work practice -- Social work practice with lesbians and gay men: working with older adults, adults with learning disabilities and adults with physical disabilities -- Social work practice with lesbians and gay men: mental health -- Social work practice with lesbians and gay men: working with children and families.
Includes bibliographical references (pages [161]-182) and index.
Keywords: Social work with lesbians; Social work with gays